2001
DOI: 10.1007/s003390000700
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of light through localized coupled-cavity modes in one-dimensional photonic band-gap structures

Abstract: Abstract. We report on the observation of a new type of propagation mechanism through evanescent coupled optical cavity modes in one-dimensional photonic crystals. The crystal is fabricated from alternating silicon-oxide/silicon-nitride pairs with silicon-oxide cavity layers. We achieved nearly full transmission throughout the guiding band of the periodic coupled cavities within the photonic band gap. The tightbinding (TB) parameter κ is determined from experimental results, and the dispersion relation, group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 17 publications
(38 reference statements)
2
33
0
Order By: Relevance
“…Recently, we reported a new type of propagation mechanism in which photons move along the localized coupledcavity modes [15,16]. Moreover, it was observed that the group velocity tends to zero and photon lifetime increases drastically at the coupled-cavity band edges [17].…”
Section: Pacsmentioning
confidence: 99%
“…Recently, we reported a new type of propagation mechanism in which photons move along the localized coupledcavity modes [15,16]. Moreover, it was observed that the group velocity tends to zero and photon lifetime increases drastically at the coupled-cavity band edges [17].…”
Section: Pacsmentioning
confidence: 99%
“…By using 1D PBG structures, potential applications concerning nonlinear optical phenomena were reported such as second harmonic generation [28], pulse compression [29], optical limiting and switching [30,31], filters [32,33], and photonic band edge lasers [34]. Moreover, the modification of spontaneous emission from atoms placed in 1D photonic band gap structures has been demonstrated [35][36][37][38][39]. Similar studies were carried out in two-dimensional photonic crystals involving light emitting diodes [40,41], and photonic crystal based lasers [42,43].…”
Section: Coupled Micro Cavity Waveguide Structures In 1d Photonic Crymentioning
confidence: 93%
“…Since high quality cavities have a crucial role in most of the photonic crystal based applications, investigation of the optical properties of cavities is essential. In recent years, coupled-microcavities have been investigated [45], and used in various applications [38,39,46,47]. These structures consist of two or more planar Fabry-Perot microcavities which are coupled to each other.…”
Section: Coupled Micro Cavity Waveguide Structures In 1d Photonic Crymentioning
confidence: 99%
“…As an example, we recently demonstrated a new type of propagation mechanism along highly localized cavity modes, i.e., photons can hop from one localized mode to the neighboring cavity modes due to interaction between these modes. [12][13][14][15] This picture can be considered as the classical wave analog of the tight-binding ͑TB͒ approximation in solid state physics. 18,19 The CCWs can be used to construct lossless and reflectionless waveguides and bends in optoelectronic components and circuits.…”
Section: -15mentioning
confidence: 99%